Insertion depth of oral stomach tubes may affect the fermentation parameters of ruminal fluid collected in dairy cows - Shen, J.S; Chai, Z; Song, L.J; Liu, J.X; Wu, Y.M (Journal of dairy science, 2012)
Six rumen-fistulated dairy cows were used in 2 trials to validate the technique for the collection of ruminal fluid by an oral stomach tube (OST). Trial 1 was conducted to compare the differences of ruminal fermentation parameters among rumen sites (cranial dorsal, cranial ventral, central, ventral, caudal dorsal, and caudal ventral). The ruminal fluid was collected once per day for 3 consecutive days through rumen cannula (RC). The samples were analyzed for pH, volatile fatty acids (VFA), ammonia N, sodium, potassium, calcium, chloride, and phosphorus concentrations. The ruminal fermentation parameters varied significantly among rumen sites. Compared with the central or ventral rumen, the cranial dorsal rumen had significantly higher pH, ammonia, and sodium concentrations and lower acetate, propionate, and butyrate concentrations, indicating that the sampling site may be one of the main factors contributing to the difference in ruminal fermentation parameters between the samples collected via the OST and RC. In trial 2, the fermentation parameters of ruminal fluid collected via OST at 2 insertion depths (180 or 200cm) were compared with those of ruminal fluid collected via RC (ventral sac). Ruminal fluid was collected once per week at 5 to 6h after morning feeding. When the OST was inserted to a depth of 180cm, the OST head was located in the cranial dorsal (atrium) of the rumen. The ruminal fluid collected via the OST had higher pH and sodium concentrations but lower VFA, potassium, calcium, and phosphorus concentrations than that collected via RC. However, when the OST was inserted to a depth of 200cm, the OST head could pass through the front rumen pillar and reach the central rumen for sampling. No differences were found in pH, VFA, ammonia N, and ion concentrations between the samples collected via the 2 sampling methods. These results indicated that the OST should be inserted to reach the central rumen to obtain representative rumen fluid samples.